Auditoria interna como instrumento de gestão pública: análise da sua utilização pela Universidade Federal da Paraíba (UFPB) e Universidade Federal do Rio Grande do Norte (UFRN) - Souza, Sérgio Ricardo Figueiredo de (2019)
The Internal Audits in the Federal Institutions of Higher Education (IFES) have become essential, given the support given to the various managerial actions of the Universities and Federal Institutes in the search for the correct execution of their budgets. Carrying out a preventive control "in loco", left aside the typically supervisory and punitive procedures and began to act effectively in management, generating administrative efficiency and contributing to the achievement of institutional objectives. Without practicing management acts, the internal audit emerges as an important tool of public management with its activities permanently focused on the evaluation of internal controls and consulting to managers. In this perspective, the general objective of the research was to analyze the use of internal audit as a public management instrument in the Internal Audit Units of the Federal University of Paraíba (UFPB) and the Federal University of Rio Grande do Norte (UFRN), and as specific objectives: to present the configuration of the structure of the Internal Audit Unit of the UFPB and the UFRN in terms of physical facilities, human resources, materials and technology; present the procedures and activities performed by the Internal Audit Units of UFPB and UFRN, taking as parameters the Management Report, the Annual Internal Audit Plan (PAINT) and the Annual Report on Internal Audit Activities (RAINT) of the respective IFES, for the years 2015, 2016 and 2017, and Evaluation Reports on Internal Audits performed by the Federal Audit Court (TCU) and the General Comptroller's Office (CGU); and present and analyze the Module: Audit and Internal Control, investigating its use by the Internal Audit of UFRN and its effects on management. With a qualitative approach, the research as to nature is characterized as descriptive, using as data collection technique the documentary, bibliographic and field research, following an observation script previously prepared and applied "in loco" at UFPB and UFRN. The results of the research showed that the internal audits, even with their developed attributions that reflect positively on the progress of the quality of public spending, with the elimination of waste and increasing improvement in the management of processes, are underutilized by managers. It was also evidenced the importance and necessary use of the Module: Internal Audit and Control, as an indispensable tool that adds value to both the management and the development of the work of the internal audit of UFRN, where we recommend its implementation in the internal audit of UFPB.